Optimal rainfall insurance contracts for maize producers in Ghana's Northern Region: A mathematical programming approach - Muamba, Francis M.; Ulimwengu, John M. (International Food Policy Research Institute, 2010)
The risk of food insecurity due to climate change in developing countries has encouraged development partners to seek new approaches to improve the resilience of subsistence agriculture to covariate shocks. Such innovative approaches include investment in safety nets such as rainfall insurance. However, a policy question remains: How does one determine the practicality of rainfall insurance for a particular district? This paper attempts to fill this gap by assessing the viability of rainfall insurance contracts for agricultural production in Ghana's Northern Region. Using a stop-loss framework, an optimal contract is determined by choosing its parameters by maximizing the objective function in the form of covariance between crop loss and indemnity payment, the objective function given a predetermined fair premium rate. The theoretical contract is implemented using monthly rainfall and annual maize crop yield data from 1998 to 2004 from 12 districts in the Northern Region under varying premium rates. We conclude that rainfall insurance may not be viable for all districts in the Northern Region; however, the contracts are likely to be viable in districts that exhibit a positive Pearson correlation coefficient between maize yield loss and indemnity payments.